The influence of compound physical exercises using a ball in the SAQ method on the concentration of lactic acid for female futsal players - Dr.Alaa Jassim Muhammad; Asst.prof. Abdullah Muhammad Taiawy; Bushra Qasim Raouf Amin (Zien Journals, 2022)
The research significance was represented in preparing compound physical exercises supported by the ball in SAQ method, and knowing the influence of such exercises upon the concentration of lactic acid for female futsal players. The research aims at revealing the influence of compound physical exercises supported by the ball in SAQ method on (lactic acid concentration) for female futsal players. The researchers hypothesized that there are statistically significant differences among the results of pre and post tests for the two experimental and control groups in (lactic acid concentration) for the female futsal players. The research also hypothesized that there were statistically significant differences among the results of the post-tests of the two experimental and control groups in (lactic acid concentration) for the female futsal players. The researchers adopted the experimental method with two groups (experimental and control) for its suitability and the nature and research problem. The research community, represented by the Kirkuk female team for futsal for the academic year (2021_2022), was selected deliberately, and they were (16) players. As for the research sample, it was chosen randomly, which consisted of (10) players representing a percentage of (62.5%) from the research community. Therefore, they were divided into two groups, control and experimental, with (5) players for each group. The researchers have reached a set of conclusions, the most important ones are: The repetition of the compound physical exercises supported by the ball of a combined nature between physical and skill in the method of SAQ and similar to the conditions of competition and in the method of high-intensity interval training showed a positive effect in the research variable for futsal players. The effect was also shown by using the compound physical exercises using the ball in SAQ method in the training units of the female futsal players. Furthermore, similar studies were conducted on males and other age groups.
Keywords: SAQ; Lactic Acid; exercise; compound